Are prosodic effects on sentence comprehension dependent on age? - Talita Fortunato-Tavares; Richard G. Schwartz; Claudia Regina Furquim de Andrade; Derek Houston; Klara Marton (CoDAS, 2023)
ABSTRACT Purpose to investigate prosodic boundary effects on the comprehension of attachment ambiguities in Brazilian Portuguese and to test two hypotheses relying on the notion of boundary strength: the absolute boundary hypothesis (ABH) and the relative boundary hypothesis (RBH). Manipulations of prosodic structure influence how listeners interpret syntactically ambiguous sentences. However, the role of prosody in spoken language comprehension of sentences has received limited attention in languages other than English, particularly from a developmental perspective. Methods Twenty-three adults and 15 children participated in a computerized sentence comprehension task involving syntactically ambiguous sentences. Each sentence was recorded in eight different prosodic forms with acoustic manipulations of F0, duration and pause varying the boundary size to reflect predictions of the ABH and RBH. Results Children and adults differed in how prosody influenced their syntactic processing and children were significantly slower than adults. Results indicated that interpretation of sentences varied according to their prosodic forms. Conclusion Neither the ABH or the RBH explained how children and adults who speak Brazilian Portuguese use prosodic boundaries to disambiguate sentences. There is evidence that the way prosodic boundaries influence disambiguation varies cross-linguistically.